Peningkatan Kreativitas dan Kompetensi Siswa dengan Menerapkan Model Discovery Learning pada Materi Perkembangan Politik dan Ekonomi pada Masa Orde Baru di Kelas XII IPS 2 SMA Negeri 1 Sijunjung - Reni Wiyarti (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2022)
History lessons learned in school are often regarded as uninteresting subjects. The condition of students when learning takes place still tends to not pay attention to the teacher's explanation, the cause of all that is because the learning process is still centered on the teacher. Students are still passive and do not have the courage to express their opinions. To improve student activity and learning outcomes, teachers are required to play an active, innovative, effective and fun role in delivering material during learning and selection of evaluations that do not only emphasize cognitive aspects, so as to increase students' interest in learning history. The formulation of the research problem is whether the use of the Discovery Learning learning model in history learning can improve learning outcomes for class XII IPS 2 SMA Negeri 1 Sijunjung in the 2021/2022 academic year. This research is a Classroom Action Research (CAR) which consists of two cycles. Each cycle consists of four stages, namely planning, action, observation or observation, and reflection. The subjects of the research were students of class XII IPS 2, totaling 30 students. Students who are said to have completed learning if students get a score equal to or more than 78 and classical completeness reach 85% of the number of students in the class. The suggestion proposed in this study is that teachers can use the Discovery Learning learning model so that it can be used as an alternative in history learning to improve the ability to ask questions, activity, interest, understanding, and student learning outcomes. In history lessons through the Discovery Learning learning model, teachers should motivate students to be more active and be able to increase students' courage in expressing opinions or ideas in the learning process.